Capacitación, preparación y superación a dirigentes de empresas - LLumbet Estanque, Isel María (2017)
Polysemy, in the definition of the concepts of training, preparation and improvement, is a limitation for its understanding and scientific development. Immersed in the aforementioned problem, was developed this research with the objective to reflect on the training process, its relationship with the preparation and improvement of business leaders, offering a theoretical position in this regard. The work groups an important volume of national and international criteria related to the subject, as necessary foundations for the educational transformations in the 21st century. Finally, some positions are taken to demonstrate a feasible path for theoretical and practical analysis that contributes to a training vision as a process increasingly organized and effective process.